Back Cover: One‐pot Conversion of Cycloalkanes to Lactones (ChemCatChem 2/2015). Issue 2 (January 2015) - Pennec, Alizé; Hollmann, Frank; Smit, Martha S.; Opperman, Diederik J.
<x xml:space="preserve">Abstract</x> The cover picture shows the one‐pot conversion of cycloalkanes to lactones. In their Communication, A. Pennec et al. describe a redox‐balanced synthetic pathway consisting of a cytochrome P450 monooxygenase (CYP450) for initial oxyfunctionalization of the cycloalkane, an alcohol dehydrogenase for ketone production and a Baeyer–Villiger monooxygenase for lactone formation. Product yields were increased by uncoupling the co‐factor requirements between the multiple oxidation reduction steps through variation of the cofactor dependence of the biocatalysts and the cofactor regeneration system. The article highlighted by this cover can be found on p. 236 ff. of Issue 2, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>